Optimalisasi Kualitas Layanan UMKM Sepatu Bungah Menggunakan SERVQUAL dan TOPSIS dengan Pendekatan Rekayasa Nilai - Silvana Mohamad; Moh. Ainul Fais; Dedy Kunhadi; Sofiyanurriyanti (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2026)
The increasingly competitive footwear MSME business environment requires business owners to improve service quality while maintaining customer satisfaction and loyalty. However, many MSMEs still face challenges related to response speed, service consistency, and personal communication. This study aims to analyze the service quality of footwear MSMEs in Bungah District using the SERVQUAL, Value Engineering, and TOPSIS approaches to determine priority strategies for service improvement. The study employed a quantitative method involving 70 customers of footwear MSMEs. The results showed that the average SERVQUAL gap was −0.75, indicating that service quality had not yet met customer expectations. The responsiveness dimension became the most critical aspect with a gap value of −1.25, followed by empathy at −1.00, while reliability had a gap of −0.60. These findings indicate that customers highly demand fast, responsive, and personalized services. Based on value engineering analysis, the service functions that contributed most significantly to quality improvement were rapid response, service accuracy, and customer communication. Furthermore, the TOPSIS method identified WhatsApp Business implementation as the top priority strategy for improving response speed, with a preference value of 0.78, followed by production and delivery scheduling with a value of 0.72. This study contributes to the development of MSME service quality improvement strategies that are more systematic, measurable, and customer-oriented.